Quality of communicating design features for cobalt chromium removable partial dentures in Riyadh, Saudi Arabia - Nassani, Mohammad Zakaria (Eur Oral Res, 2020)
PURPOSE: This survey aimed to investigate quality of communicating design features for the construction of cobalt chromium removable partial dentures (RPDs) among dentists in Riyadh, Saudi Arabia. MATERIALS AND METHODS: A survey of nine commercial dental laboratories located in Riyadh was carried out. In each visit, master casts for cobalt chromium RPDs and dentists’ prescriptions were examined. A quality score for the provided instructions was developed and ranged from 0 to 4. A zero score means that no instructions were sent from the dentist for the design of the RPD. A score of 4 means that instructions were provided for the design of four main elements of the RPD, i.e., shape of major connector, type of direct retainers, position of direct retainers, position of dental rests. RESULTS: 162 dentists’ prescriptions for RPDs and related casts were assessed. The majority of RPD cases were designed by the dental technician alone (64.2%). Shape of the major connector was the most frequent element in dentists’ prescriptions (35.8%). The mean quality score of dentists’ instructions was 0.96 (sd=1.54). 18% of the provided instructions achieved quality score equal to 4. Prescriptions for Kennedy Class III cases achieved significantly higher mean quality score compared to Kennedy Class II cases (p<0.05). 16.7% of the evaluated casts had clearly defined rest seat preparation. CONCLUSION: The results of this survey indicate inadequate quality of communicating the design features of cobalt chromium RPDs among practicing dentists in Riyadh, Saudi Arabia. The reliance on the dental technician to design the cast RPDs seems to be high.